PENGARUH KOMITE AUDIT, PROPORSI KOMISARIS INDEPENDEN, DAN PROPORSI KEPEMILIKAN INSTITUSIONAL TERHADAP TAX AVOIDANCE - Diantari, Putu Rista; Ulupui, IGK Agung (E-Jurnal Akuntansi, 2016)
The purpose of this study was to determine the effect of the audit committee, the proportion of independent directors, and the proportion of institutional ownership against tax avoidance and firm size as a control variable. In this study, tax avoidance is measured using the effective cash tax rate (CETR) companies are paying taxes divided by income before income taxes. Samples consist of manufacturing companies listed in Indonesia Stock Exchange (BEI) in the period from 2012 to 2014 totaling 44 companies. This study uses nonprobability sampling using purposive sampling technique. The analysis technique used is multiple linear regression analysis. Research results indicate that the audit committee and the proportion of independent commissioners negatively affect tax avoidance, the proportion of institutional ownership has no effect on tax avoidance, and firm size as a control variable positive effect on tax avoidance.
Keywords: Tax Avoidance, Audit Committee, Independent Commissioner, Institutional Ownership, Company Size